2015
DOI: 10.1016/j.jallcom.2015.03.035
|View full text |Cite
|
Sign up to set email alerts
|

One-step hydrothermal method to prepare nitrogen and lanthanum co-doped TiO2 nanocrystals with exposed {001} facets and study on their photocatalytic activities in visible light

Abstract: a b s t r a c tThe photocatalytic activity of TiO 2 can be mainly improved from three approaches: (1) enhancing the separation efficiency of photoelectrons and holes, (2) enhancing surface energy, and (3) increasing availability of visible light. Here, we report a one-step method to obtain nitrogen and lanthanum co-doped TiO 2 nanosheets with dominant {0 0 1} facets through a hydrothermal process, using TBOT, triethylamine and LaCl 3 ÁnH 2 O as precursor and sources of N, La respectively in HF-HNO 3 mixed aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…The 10% La-BFO photoanode absorbed more visible light than other photoanodes owing to the reduced band gap of 2.28 eV in comparison to the other materials. This will likely favour the photoelectrocatalytic degradation of the water pollutants [20,30,31]. Additionally, these band gaps are within the range of the previously reported studies of BFO [18,32].…”
Section: Uv-vis Diffuse Reflectance Spectroscopic Characterisation Of the Photoanodessupporting
confidence: 77%
“…The 10% La-BFO photoanode absorbed more visible light than other photoanodes owing to the reduced band gap of 2.28 eV in comparison to the other materials. This will likely favour the photoelectrocatalytic degradation of the water pollutants [20,30,31]. Additionally, these band gaps are within the range of the previously reported studies of BFO [18,32].…”
Section: Uv-vis Diffuse Reflectance Spectroscopic Characterisation Of the Photoanodessupporting
confidence: 77%
“…Co-alloying of anion doped TiO 2 with metal ions is another effective method for improving the visible-light photocatalytic activity of TiO 2 [363][364][365][366]. The benefits of co-alloying have been validated in numerous compositions including N/Fe 3+ , N/V 5+ , N/Sn 2+ , N/Ta 2+ , N/Ni 3+ , N/Cr 3+ , N/W 5+ , N/Ce 3+ , N/La 3+ , N/Sm 3+ and C/V 5+ [367][368][369][370][371][372][373][374][375][376][377].…”
Section: Metal Non-metal Codopingmentioning
confidence: 99%
“…Sun et al [292] and Yu et al [293] investigated the interaction between substitutional N and implanted La at the (101) and {001} facets of TiO 2 using first-principles DFT calculations and analyzed the origin of enhanced visible light photocatalytic activity of (N, La) codoped TiO 2 . They found that substitutional probability of N atom obviously decreased due to La implantation.…”
Section: N-metal Dopingmentioning
confidence: 99%